A Review of 15 Years of Corporation Tax Returns 2004 to 2018 - Lawlor, Donough; Acheson, Jean (Statistical and Social Inquiry Society of Ireland, 2021)
All companies resident in the State, with some exceptions, and all non-resident companies who trade in the State through an agency or branch are subject to corporation tax (“CT”) on gross trading profits. CT receipts account for a significant portion of Irish government revenues. The tax accounted for 21 per cent of all exchequer tax receipts in 2020, up from a low point of 10 per cent in 2011 and 15 per cent in 2004. The paper makes two new contributions. The paper presents for the first time the main trends in the headline corporate tax base variables, tax liabilities and corporation taxpayer demographics over 15 years from 2004 to 2018. The paper then uses these data to broadly examine the performance of corporation taxpayers during and after the economic crash in 2008/09, particularly with respect to profits, CT dynamics and employment levels, to provide insights on the possible performance of taxpayers during and coming out of the present crisis. This paper uses a novel CT panel dataset that allows a deeper understanding than previously available of the changing distribution and composition of the CT base, sectoral composition, key cohorts such as the top 1% and changes over time. In doing so, certain characteristics of the corporate tax base are confirmed, other trends established, and a timely analysis of the financial crisis is conducted also.
read before the Society, 17th June 2021
Keywords: corporate tax; profits; employment dynamics; 314.15